2016
DOI: 10.1021/acs.jafc.6b03904
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomes of Potato Root Exudates: Compounds That Stimulate Resting Spore Germination of the Soil-Borne Pathogen Spongospora subterranea

Abstract: Root exudation has importance in soil chemical ecology influencing rhizosphere microbiota. Prior studies reported root exudates from host and nonhost plants stimulated resting spore germination of Spongospora subterranea, the powdery scab pathogen of potato, but the identities of stimulatory compounds were unknown. This study showed that potato root exudates stimulated S. subterranea resting spore germination, releasing more zoospores at an earlier time than the control. We detected 24 low molecular weight org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…The inoculum was approximately 1 year old when used. Inoculum contained approximately 6900 sporosori mg À1 , as determined by suspending 0.1 g of inoculum in 10 mL of water and quantifying using a haemocytometer under light microscopy (Balendres et al, 2016a).…”
Section: Preparation Of S Subterranea Inoculummentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculum was approximately 1 year old when used. Inoculum contained approximately 6900 sporosori mg À1 , as determined by suspending 0.1 g of inoculum in 10 mL of water and quantifying using a haemocytometer under light microscopy (Balendres et al, 2016a).…”
Section: Preparation Of S Subterranea Inoculummentioning
confidence: 99%
“…Previous studies (Ledingham, 1934;Kole, 1954;Merz, 1989Merz, , 1992Merz, , 1997 indicated that zoospore release could be stimulated by incubation of resting spores in Hoagland's solution (HS). The first direct measurement of stimulation of zoospore release by HS was recently reported, but the specific chemical(s) involved was not determined (Balendres et al, 2016a).…”
mentioning
confidence: 99%
“…Individual disease lesions were excised using a scalpel, oven‐dried for 4 days at 40°C, ground to a powder with a mortar and pestle and stored at 4°C until use. The inoculum contained an estimated 6,900 sporosori mg −1 determined by suspending 0.1 mg of inoculum in 10 ml water and enumerating using a haemocytometer with a light microscope (DM 2500 LED; Leica Microsystem, Germany; Balendres et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The pathogen persists in the soil as dormant resting spores aggregated as clusters known as sporosori (Balendres, Tegg, & Wilson, ). Pathogenicity initiates with the germination of the resting spores stimulated by host plant root exudates resulting in the release of short‐lived primary zoospores into the soil (Balendres, Clark, Tegg, & Wilson, ; Balendres, Nichols, Tegg, & Wilson, ). Released zoospores migrate towards roots of susceptible hosts, aided most likely by chemotaxic attraction to root exudates, where they encyst and transfer their cell contents into the root epidermis cell.…”
Section: Introductionmentioning
confidence: 99%
“…Powdery scab and root galling susceptibility differ across potato cultivars (Bittara et al, 2016;Falloon et al, 2003), but no genetic basis of resistance has yet been identified. Metabolites of potato root exudates induce S. subterranea resting spore germination, but as L-glutamine and tyramine have the strongest effects, this might not be host specific (Balendres et al, 2016). This may explain reports of primary infection by S. subterranea in a range of nonsolanaceous host plants (Merz and Falloon, 2009).…”
Section: Spongospora Subterraneamentioning
confidence: 99%